An Evidence‐Based, Community‐Engaged Approach to Develop an Interactive Deliberation Tool for Pediatric Neuromuscular Trials. Issue 2 (20th December 2017) - Moultrie, Rebecca R.; Lewis, Megan A.; Paquin, Ryan S.; Lucas, Ann; Jarecki, Jill; Peay, Holly L.
Abstract: Duchenne/Becker muscular dystrophy (DBMD) and spinal muscular atrophy (SMA) are rare neuromuscular disorders that present challenges to therapeutic and clinical trial decision making. We developed an interactive, evidence‐based online tool designed to encourage thoughtful deliberation of the pros and cons of trial participation and to inform meaningful discussions with healthcare providers. Prior research demonstrates the importance of tool availability at the time each family is considering trial participation, which may be prior to the informed consent process. The tool is intended to be easily modified to other pediatric disease communities. Tool development was informed by prior qualitative research, literature reviews, and stakeholder input. Specific items were derived based on an online exploratory questionnaire of parents whose children participated in a trial for DBMD or SMA to understand motivations for participation. Parent participants in the exploratory survey reported strong impact of altruistic and individual benefit motivations and placed much greater emphasis on anticipated trial benefits than on harms when making participation decisions. We used this data to develop the evidence‐based deliberation tool using a community‐engaged approach. We initially targeted the tool for DBMD while using SMA survey data to evaluate ease of transition to that population. We conducted two iterative sets of activities to inform development and refinement of the tool: (1) community engagement of key stakeholders and (2) user experience testing. These activities suggest that the tool may increase deliberation and the weighing of benefits and harms. Ongoing evaluation will determine the acceptability and efficacy of this online intervention.